MENAPAKI SEJARAH PEMIKIRAN DALAM TEOLOGI ISLAM - Huda, Nurul; Adnan, Mohammad (CENDEKIA: Jurnal Studi Keislaman, 2020)
When the Prophet was still alive, all problems faced by the companions were always asked directly to the Prophet. At that time the Prophet was a central thought of Muslims at that time. The question at that time was not only limited to religious issues, but almost all the problems of the Companions were asked to the Messenger of Allah and immediately answered all the problems that were asked to the Prophet. However, after the death of the Messenger of Allah the direction of thinking about a problem moved to the Companions, but in different contexts there were unresolved problems at the hands of the Companions. So in its journey, then when the problem of theological concepts occurred, it was then that they found a dead end. That is why then those who disagree with regard to theological problems then seek and find their own concepts based on their respective understandings. For this reason, this article tries to review a few of these thoughts